ANALISA PENGARUH SOLVABILITAS, PROFITABILITAS, TOTAL ASSET, UMUR PERUSAHAAN, TERHADAP AUDIT DELAY PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Ade Trisyanto (Jurnal Buana Akuntansi, 2019)
auditor of the company until the close of the audit report was signed. The purpose of this study fatherly influence obtain empirical evidence of solvency, profitability, total assets, age perusahaa on the Audit Delay. This study is a descriptive causal research that aims to determine the effect of causation of the independent variabel on the dependent variabel. The level of intervention the researchers in this study are minimal intervention since researchers only collected data from the company's audited financial statements without manipulating the data. Unit analisiss in this study dalah companies listed on the Indonesia Stock Exchange. This study was a cross-sectional studies for the research carried out at from time to time, the company's audited financial statement data of the manufacturing sector. The object of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2010-2014 reporting using the rupiah currency and the US dollar have been converted into rupiah. With the number of samples obtained as many as 397 companies that have been determined by purposive sampling method. Data analysis techniques that make use of multiple linear regression premises classic assumption test, F test and t test. The results of this study are variabel solvency and total assets of the company do not affect the Audit Delay, while profitability and firm age effect on Audit Delay. Keywords: solvency, profitability, total assets, the age of the company, the Audit Delay